Metadiscipline approach to foreign language education - Дудоладова, А. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The article is devoted to the problem of a metadiscipline approach. The article considers the essence and components of a metadiscipline approach in education, the possibility of its integration into the process of teaching foreign languages, as well as analysis of metadiscipline skills in foreign language education. The essence of a “metadiscipline approach”, “metadiscipline knowledge”, “metadiscipline skills” and “metacognitive strategies” has been studied.The article is aimed at studying the metadisciplinary phenomenon within the training of future foreign language teachers and interpreters, in particular in the process of their work connected with the analysis of authentic texts. The essence of their competence is viewed through the metadiscipline approach that proves to be essential in facilitating the formation of universal skills which are believed to be an integral part of the identity of a foreign language learner. The ways to integrate the metadiscipline approach into foreign language education have been clarified on the basis of latest research in the methods of teaching. The author has undertaken an attempt at theorizing a wide range of possibilities to put the above-mentioned ways into practice of foreign language teaching. The nature of individual work has been accentuated, with an emphasis on the cognitive activity that participates in developing metadiscipline skills. With the essence of the metadisciplinary phenomenon being investigated in the article, special attention is paid to considering metacognitive strategies in the process of teaching a foreign language in linguistic institutions of higher education. Potential lines of investigating the metadisciplinary phenomenon in foreign language teaching have been identified.